Association of low ficolin-2 concentration in cord serum with respiratory distress syndrome in preterm newborns - Gajek, Gabriela; Świerzko, Anna S.; Jarych, Dariusz; Mikulski, Damian; Kobiela, Paulina; Chojnacka, Karolina; Kufelnicka-Babout, Maja; Szala-Poździej, Agnieszka; Chrzanowski, Jędrzej; Sobczuk, Katarzyna; Fendler, Wojciech; Matsushita, Misao; et al. (Frontiers in Immunology, 2023)
Introduction: Ficolin-2 is a serum pattern recognition molecule, involved in complement activation via the lectin pathway. This study aimed to investigate the association of ficolin-2 concentration in cord blood serum with complications related to premature birth. Methods: 546 premature neonates were included. The concentration of ficolin-2 in cord blood serum was determined by a sandwich TRIFMA method. FCN2 genetic variants were analysed with RFLP-PCR, allele-specific PCR, Sanger sequencing or allelic discrimination using TaqMan probes method. Findings: Cord blood serum ficolin-2 concentration correlated positively with Apgar score and inversely with the length of hospitalisation and stay at Neonatal Intensive Care Unit (NICU). Multivariate logistic regression analysis indicated that low ficolin-2 increased the possibility of RDS diagnosis [OR=2.05, 95% CI (1.24-3.37), p=0.005]. Median ficolin-2 concentration was significantly lower in neonates with RDS than in premature babies without this complication, irrespective of FCN2 gene polymorphisms localised to promoter and 3’untranslated regions: for patients born <33 GA: 1471 ng/ml vs. 2115 ng/ml (p=0.0003), and for patients born ≥33 GA 1610 ng/ml vs. 2081 ng/ml (p=0.012). Ficolin-2 level was also significantly lower in neonates requiring intubation in the delivery room (1461 ng/ml vs. 1938 ng/ml, p=0.023) and inversely correlated weakly with the duration of respiratory support (R=-0.154, p<0.001). Interestingly, in the neonates born at GA <33, ficolin-2 concentration permitted differentiation of those with/without RDS [AUC=0.712, 95% CI (0.612-0.817), p<0.001] and effective separation of babies with mild RDS from those with moderate/severe form of the disease [AUC=0.807, 95% CI (0.644-0.97), p=0.0002]. Conclusion: Low cord serum ficolin-2 concentration (especially in neonates born at GA <33 weeks) is associated with a higher risk of developing moderate/severe RDS, requiring respiratory support and intensive care.